Image-Based Mobile System for Dietary Management in an American Cardiology Population: Pilot Randomized Controlled Trial to Assess the Efficacy of Dietary Coaching Delivered via a Smartphone App Versus Traditional Counseling - Choi, Brian G; Dhawan, Tania; Metzger, Kelli; Marshall, Lorraine; Akbar, Awdah; Jain, Tushina; Young, Heather A; Katz, Richard J (JMIR Publications, 2019)
BackgroundRandomized controlled trials conducted in Mediterranean countries have shown that the Mediterranean diet lowers adverse cardiovascular events. In the American population, diet remains the biggest uncontrolled risk factor for cardiovascular disease. ObjectiveThis study aimed to test the hypothesis that asynchronous dietary counseling supplied through a custom smartphone app results in better adherence to a Mediterranean diet in a non-Mediterranean population than traditional standard-of-care (SOC) counseling. MethodsIn total, 100 patients presenting to the cardiology clinic of an academic medical center were randomized to either the SOC or smartphone app-based experimental (EXP) Mediterranean diet intervention after informed consent and 1 hour of individual face-to-face dietary counseling with a registered dietitian. Participants in EXP received a custom smartphone app that reinforced the Mediterranean diet, whereas participants in SOC received 2 additional sessions of in-person dietary counseling with the registered dietitian-30 min at 1 month and 30 min at 3 months. Preexisting knowledge of a Mediterranean diet was measured by the validated Mediterranean Diet Score (MDS) instrument. Baseline height, weight, blood pressure (BP), and laboratory biomarkers were collected. At 1, 3, and 6 months, participants presented for a follow-up appointment to assess compliance to the Mediterranean diet using the MDS as well as a patient satisfaction survey, BP, and weight. Repeat laboratory biomarkers were performed at 3 and 6 months. ResultsEnrolled participants had a mean age with SE of 56.6 (SD 1.7) for SOC and 57.2 (SD 1.8) for EXP; 65.3% of SOC and 56.9% of EXP were male, and 20.4% of SOC and 35.3% of EXP had coronary artery disease. There were no significant differences between EXP and SOC with regard to BP, lipid parameters, hemoglobin A1c, or C-reactive protein (CRP). Participants in EXP achieved a significantly greater weight loss on average of 3.3 pounds versus 3.1 pounds for participants in SOC, P=.04. Adherence to the Mediterranean diet increased significantly over time for both groups (P<.001), but there was no significant difference between groups (P=.69). Similarly, there was no significant difference in diet satisfaction between EXP and SOC, although diet satisfaction increased significantly over time for both groups. The proportion of participants with high Mediterranean diet compliance (defined as the MDS ≥9) increased significantly over time (P<.001)-from 18.4% to 57.1% for SOC and 27.5% to 64.7% for EXP; however, there was no significant difference between the groups. ConclusionsBoth traditional SOC counseling and smartphone-based counseling were effective in getting participants to adhere to a Mediterranean diet, and these dietary changes persisted even after counseling had ended. However, neither method was more effective than the other. This pilot study demonstrates that patients can change to and maintain a Mediterranean diet with either traditional or smartphone app-based nutrition counseling. Trial RegistrationClinicalTrials.gov NCT03897426;https://clinicaltrials.gov/ct2/show/NCT03897426